2002
DOI: 10.1063/1.1478773
|View full text |Cite
|
Sign up to set email alerts
|

Complex dynamics in a simple model of pulsations for super-asymptotic giant branch stars

Abstract: When intermediate mass stars reach their last stages of evolution they show pronounced oscillations. This phenomenon happens when these stars reach the so-called Asymptotic Giant Branch (AGB), which is a region of the Hertzsprung-Russell diagram located at about the same region of effective temperatures but at larger luminosities than those of regular giant stars. The period of these oscillations depends on the mass of the star. There is growing evidence that these oscillations are highly correlated with mass … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 37 publications
(45 reference statements)
1
11
0
Order By: Relevance
“…In the absence of a better explanation, it was attributed to long-term (secular) nonlinear effects in the stellar envelopes. In a previous work [6], we have shown that our simple model recovers such a behaviour as it is generic of Hamiltonian systems. We also presented clear examples of sticky orbits together with an extensive discussion of their implications in the framework of the classification of variable stars.…”
Section: Formation Of the Stochastic Seasupporting
confidence: 61%
See 1 more Smart Citation
“…In the absence of a better explanation, it was attributed to long-term (secular) nonlinear effects in the stellar envelopes. In a previous work [6], we have shown that our simple model recovers such a behaviour as it is generic of Hamiltonian systems. We also presented clear examples of sticky orbits together with an extensive discussion of their implications in the framework of the classification of variable stars.…”
Section: Formation Of the Stochastic Seasupporting
confidence: 61%
“…In the present work we have extended the preliminary results of Ref. [6] concerning the dynamics of a forced oscillator as a model of irregular stellar pulsations. The driving is characterized by two parameters, the fractional amplitude of the internal perturbation α and the total amplitude of the driving ǫ.…”
Section: Discussionmentioning
confidence: 56%
“…The values of ω used in their work were equivalent to adopting stellar models in the family of low‐mass stars ( M ≤ 5–8 M ⊙ ) reaching the AGB. In a recent publication (Munteanu et al 2002), we extended their conclusion to intermediate‐mass stars (8 M ⊙ ≤ M ≤ 11 M ⊙ ) also in the AGB phase, more precisely to values of ω around 3. In the previous sections, we have shown that in the case of ω= 20.1 a peculiar behaviour is born from the interplay between non‐adiabaticity and internal perturbation.…”
Section: Numerical Resultsmentioning
confidence: 80%
“…The one‐zone model approach is especially suited for AGB stars as the density difference between the central core and the outer layers is so large that these two regions can be considered as effectively decoupled. Following Icke, Frank & Heske (1992) and Munteanu et al (2002), we consider the stellar pulsation to be simulated by a variable inner boundary located well beneath the photosphere and moving with constant frequency (piston approximation). This sinusoidal driving consists of pressure waves originating in the interior and propagating through a transition zone until they dissipate in the outer layers.…”
Section: The One‐zone Modelmentioning
confidence: 99%
“…[2] Some basic concepts used throughout the paper are reviewed in Appendix A. Nontwist maps are used to describe many physical systems, e.g., magnetic field lines in tokamaks (see, e.g., Refs. [3][4][5][6][7][8][9]) and stellarators [10,11] (plasma physics); planetary orbits, [12] stellar pulsations [13] (astronomy); traveling waves, [1,14] coherent structures and selfconsistent transport [15] (fluid dynamics). Additional references can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%